Pengaruh Informasi Produk dan Harga terhadap Urutan Kesukaan Produk Susu Cokelat Siap Minum pada Konsumen Anak-Anak - Dede Robiatul Adawiyah; Amalia Rakhmadani; Lince Lince (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2023)
Milk consumption in Indonesia decreased from 3.53 in 2020 to 2.72 kg per capita per year in 2021, prompting the food industry to enhance their products to increase milk consumption and gain a wider market. The hedonic ranking test requires panelists to rank the samples from most preferred to least preferred. Studies on food preferences have involved children to obtain accurate data for child consumers. This research aimed to determine the effect of price and product form information on the preference for chocolate milk products among children consumers. The samples consisted of four chocolate milk products in powder and ready-to-drink forms from two producers. The study recruited 120 children (46 boys and 74 girls aged 10-12 years) from schools in Jabodetabek. The hedonic ranking test method was used in three presentation types: (1) blind test (without additional information) 1 and 2, (2) price test, and (3) price test with product form information. Data analysis involved the Friedman test and LSD rank. Results indicated that the blind test 1, blind test 2, and price test showed a significant difference in preference at a significance level of 0.05. However, the price test with product form information did not demonstrate any significant differences in preferences, although some samples changed their ranking, specifically ready-to-drink milk. The milk drink with the lowest price was ranked 2.